Optimum interaction of light intensity and CO2 concentration in bioremediating N-rich real wastewater via assimilation into attached microalgal biomass as the feedstock for biodiesel production - Rosli, S.S. (Institution of Chemical Engineers, 2020)
Impoverishing nutrients from wastewater via assimilation into microalgal biomass has gained footprint in bioremediation technologies. To ease the harvesting of mature microalgal biomass from effluent, this study proposed the employment of fluidized bed bioreactor to grow attached microalgal biomass onto polyurethane foam support material while bioremediating the N-rich real wastewater from chemical fertilizer manufacturing industry. The complete removals of all nitrogen species (NH4+-N, NO2â-N and NO3â-N) together with COD and total phosphorus were achieved at the optimum light intensity and CO2 concentration of 216 Î¼mol/m2 s and 9.1 , respectively, giving rise to the attached microalgal biomass productivity of 0.094 g/L/day. These performances were also found maintaining for at least 4 cycles of reiterative uses of spent polyurethane foam support material in similar fluidized bed bioreactor setup condition with every cycle being introduced with fresh N-rich real wastewater. The mechanism of attachment formations study predicted that the polysaccharides and proteins from microalgal extracellular polymeric substances had bridged the cells onto polyurethane foam support material during the initial colonization prior to populating and growing to cover the surfaces of support material. For biodiesel production, the extracted neutral lipid content of attached microalgal biomass was found to be four times higher than the suspended growth culture. From the transesterification process, about 97 â98 of attached microalgal lipid could be converted into fatty acid methyl esters (FAMEs) mixture. Interestingly, the degree of saturated fatty acids (SFA) in FAMEs was recorded increasing with the increase of cycles of reusing spent polyurethane foam support material. The presence of more SFA in FAMEs could overall enhance the oxidative stability and contribute to higher cetane number of produced biodiesel from facilely harvested attached microalgal biomass. Â© 2020 Institution of Chemical Engineers